Cognition and Behavioral Effects in Epilepsy: A Review: Cognition and Behavioral Effects in Epilepsy: A Review - Sravanthi, K. (International Journal of Pharmaceutical & Biological Archive, 2020)
Epilepsy is a chronic neurological disorder which is caused by various factors which may vary according to the age of patients which results in asynchronization of neurons. Cognitive functional impairment is mostly seen in epileptic patients compared to the general population, and the degree of its impairment varies from one another according to the epilepsy syndrome. Behavioral changes are more seen in epileptic people and people with drug-resistant epilepsy, frequent seizures, and associated neurological or mental abnormalities. In children and adults, many data suggest a correlation between behavior/cognition and some other specific epilepsy syndromes. The major predictors of such behavioral changes in children with epilepsy are epilepsy itself, treatment, the underlying structural lesion, and epilepsy treatment.